2017
DOI: 10.1111/acel.12581
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of heart failure and frailty: a common inflammatory origin?

Abstract: SummaryFrailty, a clinical syndrome that typically occurs in older adults, implies a reduced ability to tolerate biological stressors. Frailty accompanies many age‐related diseases but can also occur without overt evidence of end‐organ disease. The condition is associated with circulating inflammatory cytokines and sarcopenia, features that are shared with heart failure (HF). However, the biological underpinnings of frailty remain unclear and the interaction with HF is complex. Here, we describe the inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 83 publications
1
78
1
3
Order By: Relevance
“…Frailty, which is characterized by a state of decreased physical activity and poor endurance, has been associated with clinical CVD (Bellumkonda et al 2017). As a result, it is possible that CMV infection also results in frailty via chronic inflammation and/or CVD.…”
Section: And Frailtymentioning
confidence: 99%
“…Frailty, which is characterized by a state of decreased physical activity and poor endurance, has been associated with clinical CVD (Bellumkonda et al 2017). As a result, it is possible that CMV infection also results in frailty via chronic inflammation and/or CVD.…”
Section: And Frailtymentioning
confidence: 99%
“…The exact cause of why frailty is related to adverse outcomes remains unknown. However, it may be attributable to the systemic effects of cardiovascular disease, such as activation of inflammatory and neurohumoral processes and limitation of physical activity[ 11 ]. Such mechanisms may lead to worse clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition, chronic inflammation, mitochondrial dysfunction, hormonal changes, and declines in neural function have been observed to play roles in the decrease of skeletal muscle mass and strength, leading to the development of sarcopenia . Recently, it has been reported that similar pathophysiological mechanisms contribute to cardiac dysfunction, including mitochondrial dysfunction, inflammation, and malnutrition, which implies that these factors could influence smooth muscle function as well as skeletal muscle function. Moreover, it was demonstrated that sarcopenia could worsen the functioning of the autonomic nervous system .…”
Section: Discussionmentioning
confidence: 99%